2012
DOI: 10.1007/s10745-011-9451-6
|View full text |Cite
|
Sign up to set email alerts
|

Group Forest Certification for Smallholders in Vietnam: An Early Test and Future Prospects

Abstract: Forests in Vietnam are heavily utilized resources. Some 25 million people who live in and near forests depend on timber and non-timber resources for subsistence and income. Vietnam's timber processing industries, which are in a steep growth phase, demand raw material from the nation's forests, but that demand greatly outstrips available, high quality supply. A national forest development strategy through 2020 calls for broad expansion of plantation forests coupled with third-party forest certification. One typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…Studies of FSC and Rainforest Alliance operations have found that the costs of accessing certification outweigh the benefits, meaning low uptake of FSC in developing countries (Marx and Cuypers, 2010) and among smallholders (Auer, 2012;Gullison, 2003;McDermott et al, 2015), and a bias towards large producers (McDermott et al, 2015;Pinto and McDermott, 2013). Scholars show that in order for PES and REDD+ schemes to target those who are most able to (competitively) provide services, access to schemes has often been restricted to those with appropriate assets such as land (Porras et al, 2008) or education (Zbinden and Lee, 2005), favouring larger operations and wealthier farmers (Pagiola and Platais, 2007) and reducing opportunities for women (Boyd, 2002;Lee et al, forthcoming).…”
Section: Governance Beyond the State: Markets And Non-state Actorsmentioning
confidence: 99%
“…Studies of FSC and Rainforest Alliance operations have found that the costs of accessing certification outweigh the benefits, meaning low uptake of FSC in developing countries (Marx and Cuypers, 2010) and among smallholders (Auer, 2012;Gullison, 2003;McDermott et al, 2015), and a bias towards large producers (McDermott et al, 2015;Pinto and McDermott, 2013). Scholars show that in order for PES and REDD+ schemes to target those who are most able to (competitively) provide services, access to schemes has often been restricted to those with appropriate assets such as land (Porras et al, 2008) or education (Zbinden and Lee, 2005), favouring larger operations and wealthier farmers (Pagiola and Platais, 2007) and reducing opportunities for women (Boyd, 2002;Lee et al, forthcoming).…”
Section: Governance Beyond the State: Markets And Non-state Actorsmentioning
confidence: 99%
“…This research has focused on the impacts of certification (Hain and Ahas 2007;Cubbage et al 2010;Sugiura et al 2012), environmental appropriateness (Tacconi et al 2004), price premium (Koller and Lagan 2007;Zhao et al 2011;Auer 2012), and the motivations of certification adopting (Araujo et al 2009). However, most of these studies were based on experience obtained in developed countries located in Europe and North America.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the finding for certification in the developing countries (Kollert and Lagan, 2007, Nebel et al, 2005, Auer, 2012, mandatory certification has not resulted in economic benefits. The results indicated after two years holding certification, there is no significant improvement in market access or timber price.…”
Section: The Lack Of Economic Benefitsmentioning
confidence: 80%
“…Certification cost is one of the most important barrier of certification program in tropical developing countries (Auer, 2012, Durst et al, 2006. These barriers can come from the internal or external of forest management unit.…”
Section: Forest Certification In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation